A study on the factor that influence internal promotion in Majlis Daerah Kuala Selangor - Supandi, Nur Izyan (2012)
The researcher is investigating the factors that influence the potential candidates from inside organization which is the employees in filling the vacancies. The employer usually makes internal promotion to increase the motivation of employees. Increasing in promotion of the employees make the employer realize how important promotion to the organization. This study was conducted in Majlis Daerah Kuala Selangor (MDKS) which is the employees selected as population. MDKS has 400 employees and 210 selected as sample size. The entire population has probability selected as respondents because the researcher using Simple Random Sampling. This study found out those three independent variables which are employees’ characteristics, work stability and training has relationship that can contribute to internal promotion. But, employees’ characteristic which is job tenure is most influence factor for internal promotion.